Photo-Fenton degradation on Mo-doped NiFe2O4 photocatalyst - Shrivastava A.; Kumar U.; Sinha I. (My University, 2025)
The poor photo-Fenton properties of NiFe2O4, a magnetic material, can be altered by appropriate metal ion doping. We carried out preliminary DFT and TD-DFT calculations and found that the photoexcited molybdenum doped NiFe2O4 interacts effectively with H2O2 for hydroxyl radical generation. Based on this prediction, we prepared Mo-doped NiFe2O4 and tested its photo-Fenton activity for tetracycline (TC) degradation. The Mo-doped NiFe2O4 nanoparticles were significantly finer in size and superparamagnetic, enabling easy after-use separation. Experimental and DFT calculation results showed that the Mo-dopant substitutes the Fe3+ occupying the octahedral site in NiFe2O4. Mo-doping extended the absorption edge and decreased the interfacial charge transfer resistance of NiFe2O4. The Mo-doped NiFe2O4 nanoparticles demonstrated excellent TC photo-Fenton degradation activity, along with appropriate recyclability. A combination of experimental and DFT calculation results indicated the possible photo-Fenton mechanism. © 2025 The Royal Society of Chemistry.